Village Development through Hydropower - Pradhan, Gyanendra Lal (Hydro Nepal: Journal of Water, Energy and Environment, 2010)
This paper proposes a new model to develop small hydropower on the Public-Private Partnership (PPP) model, by developing one small hydro project in a district under the auspices of local institutions such as the District Development Committee (DDC), Village Development Committee (VDC), municipality, etc., in partnership with an entrepreneur or the Federation of Nepalese Chambers of Commerce and Industries. This model will create wealth for the villages of the district; and local institutions need not look to the Nepal government for the development grant. Hydropower is the best means to bring in development that the local people aspire for. As hydro development requires infrastructure building of roads, transmission lines etc., it will open the door of opportunity in the district for rapid growth. At the beginning, 1-5 MW size is proposed and in later stages larger sizes can be attempted. As the entrepreneur puts in equity at the beginning, and only after project operation, shares are given to the locals. A share structure of 70:30 is proposed for the entrepreneur and the local institutions respectively. Key words: Public-Private Partnership; Small hydropower; Nepal DOI: 10.3126/hn.v5i0.2492 Hydro Nepal Vol. 5, July 2009 Page:54-55